Does Cash Turnover and Total Asset Turnover Affect the Net Profit Margin at PT Bank Jabar Banten Syariah for the 2013-2022 Period? - Anggarani, Dewi; Marlina, Lina; Andani, Listia (Review of Islamic Economics and Finance, 2024)
Purpose – This research is motivated by the discrepancy between theory and reality, where in theory it is said that when cash turnover and total asset turnover increase, net profit margin will increase and vice versa. This study aims to determine how cash turnover, total asset turnover and net profit margin at PT BJB Syariah for the period 2013-2022 and to find out how cash turnover and total asset turnover affect net profit margin at PT BJB Syariah for the period 2013-2022 partially and simultaneously.Methodology - This research uses quantitative methods using IBM SPSS Statistics 26 analysis tools with purposive sampling technique, based on appropriate considerations by taking into account the criteria with several limitations taken in this research. The data used in this study are secondary data in the form of quarterly financial reports of PT BJB Syariah for the period 2013-2022. The independent variables used are cash turnover and total asset turnover, and the dependent variable used is net profit margin. The tests carried out are by analyzing descriptive statistics, classical assumption test and multiple linear regression analysis. Findings - The results of this study indicate that partially cash turnover has a significant positive effect on net profit margin. Then total asset turnover has a significant negative effect on the net profit margin. While simultaneously cash turnover and total asset turnover have a significant positive effect on net profit margin. This research shows that BJBS needs to make strategy adjustments to increase profitability by considering asset management decisions and operational strategies.Keywords: Cash Turnover; Total Asset Turnover; Net Profit Margin